Synthesis, band gap structure and third order non-linear optical properties of zinc tungsten oxide nanocomposite using a single CW laser beam - Jalili, Zahra; Koushki, Ehsan; Ehsanian, Amir Hossein; Tayebee, Reza; Maleki, Behrooz (Frontiers in Chemistry, 2023)
In this study, a composite of zinc tungsten oxide nanoparticles (W-ZnO NPs) has been synthesized via mixing Na2WO4 and zinc acetate in water, followed by dropwise addition of NaOH. The synthesized W-ZnO NPs were characterized using measurement methods such as XRD, dynamic light scattering (DLS), Scanning electron microscopy (SEM) and UV-Vis. Also, the results were compared with the pure synthesized ZnO and WO3 NPs. Non-linear optical properties of the synthesized composite were measured using the Z-scan technique with a continuous wave Nd-Yag laser. The negative non-linear absorption coefficient of the components was obtained which indicates that the saturation absorption occurred in this composite. In comparison with pure ZnO NPs, non-linear absorption decreases which can be attributed to the negligible optical response of WO3 structures. Also, the negative value of the close aperture Z-scan curve shows that the thermal lensing effect is the main reason for the third-order non-linear refraction.